Surface Enrichment in Equimolar Mixtures of Non-Functionalized and Functionalized Imidazolium-Based Ionic Liquids - Heller, Bettina; Kolbeck, Claudia; Niedermaier, Inga; Dommer, Sabine; Schatz, Jürgen; Hunt, Patricia; Maier, Florian; Steinrück, Hans-Peter (ChemPhysChem, 2018)
For equimolar mixtures of ionic liquids with imidazolium-based cations of very different electronic structure, we observe very pronounced surface enrichment effects by angle-resolved X-ray photoelectron spectroscopy (XPS). For a mixture with the same anion, that is, 1-methyl-3-octylimidazolium hexafluorophos phate+1,3-di(methoxy)imidazolium hexafluorophosphate ([C8C1Im][PF6]+[(MeO)2Im][PF6]), we find a strong enrichment of the octyl chain-containing [C8C1Im]+ cation and a correspond ing depletion of the [(MeO)2Im]+ cation in the topmost layer. For a mixture with different cations and anions, that is, [C8C1Im] [Tf2N]+[(MeO)2Im][PF6], we find both surface enrichment of the [C8C1Im]+ cation and the [Tf2N]@ (bis[(trifluoromethyl)sulfonyl] imide) anion, while [(MeO)2Im]+ and [PF6]@ are depleted from the surface. We propose that the observed behavior in these mixtures is due to a lowering of the surface tension by the enriched components. Interestingly, we observe pronounced differences in the chemical shifts of the imidazolium ring signals of the [(MeO)2Im]+ cations as compared to the non-functional ized cations. Calculations of the electronic structure and the intramolecular partial charge distribution of the cations contrib ute to interpreting these shifts for the two different cations.

Surface Enrichment in Equimolar Mixtures of Non-Functionalized and Functionalized Imidazolium-Based Ionic Liquids - Heller, Bettina; Kolbeck, Claudia; Niedermaier, Inga; Dommer, Sabine; Schatz, Jürgen; Hunt, Patricia; Maier, Florian; Steinrück, Hans-Peter (ChemPhysChem, 2018)
Keywords: density functional theory; electronic structure; angle-resolved X-ray photoelectron spectroscopy (ARXPS); ionic liquid mixture; surface science

Suzuki cross-coupling in aqueous media - Hoffmann, Ina; Blumenröder, Bettina; Onodi, Silvia; Dommer, Sabine; Schatz, Jürgen (Green Chemistry, 2015)
We report a simple and efficient procedure for the ligand-free as well as ligand-assisted Suzuki reaction in both pure water and aqueous media. The cross-coupling reactions proceed successfully using phenylboronic acid or potassium phenyltrifluoroborate as a nucleophilic coupling partner. The method can be effectively applied to both activated and deactivated aryl halides yielding quantitative conversions. The catalytic activity of couplings performed in pure water increases when utilizing supramolecular additives, but decreases under standard phase-transfer conditions. Finally, the palladium loading is reducible from 3.0 mol% to 0.4 mol% without any loss of conversion.